2004
DOI: 10.1021/jp049194l
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hydrodenitrogenation on Phosphides and Sulfides

Abstract: The mechanism of hydrodenitrogenation (HDN) of 2-methylpiperidine was studied over a silica-supported nickel phosphide catalyst (Ni2P/SiO2, Ni/P = 1/2) and a commercial Ni-Mo-S/Al2O3 catalyst in a three-phase trickle-bed reactor operated at 3.1 MPa and 450-600 K. Analysis of the product distribution as a function of contact time indicated that the reaction proceeded in both cases predominantly by a substitution mechanism, with a smaller contribution of an elimination mechanism. Fourier transform infrared spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 58 publications
1
39
0
3
Order By: Relevance
“…Because it is important that the organic N-compound, such as the alkyl amine should bind near to the site where the H 2 is activated it was argued that at least a fraction of the P-OH groups must belong to the active hydrogenation phase to promote the interaction of the hydrogen and the nitrogen base [22,37]. It was suggested that the hydroxyl groups would come from phosphate species of the passivated catalyst that did not become fully reduced in the activation treatment by H 2 .…”
Section: Catalyst Topologymentioning
confidence: 99%
“…Because it is important that the organic N-compound, such as the alkyl amine should bind near to the site where the H 2 is activated it was argued that at least a fraction of the P-OH groups must belong to the active hydrogenation phase to promote the interaction of the hydrogen and the nitrogen base [22,37]. It was suggested that the hydroxyl groups would come from phosphate species of the passivated catalyst that did not become fully reduced in the activation treatment by H 2 .…”
Section: Catalyst Topologymentioning
confidence: 99%
“…Recent studies showed that supported Ni 2 P catalysts had considerable HDN activity also in absence of sulfur [8][9][10][11]. With the aim to generate knowledge about the HDN processes of feeds containing aliphatic N-compounds in high concentration and virtually no sulfur we studied the catalytic HDN reaction of simple compounds, representing the Norganic molecules of MBM pyro-oil, over supported Ni 2 P catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…A reakciósebesség meghatározó lépése általában a telített gyűrű C-N kötésének hidrogenolízise. A C-N kötés felszakadásának legvalószínűbb kezdeti lépése Ni 2 P katalizátoron a heterociklus aktiválása α pozícióban [6,7,53], amit később E 2 elimináció vagy S N 2 nukleofil szubsztitúció követhet. Az utóbbi S N 2 mechanizmus akkor lehetséges, ha a heterogyűrű N atomja elleni támadás sztérikusan nem gátolt [6,7,53].…”
Section: A Hdn Reakciók Mechanizmusaunclassified
“…A C-N kötés felszakadásának legvalószínűbb kezdeti lépése Ni 2 P katalizátoron a heterociklus aktiválása α pozícióban [6,7,53], amit később E 2 elimináció vagy S N 2 nukleofil szubsztitúció követhet. Az utóbbi S N 2 mechanizmus akkor lehetséges, ha a heterogyűrű N atomja elleni támadás sztérikusan nem gátolt [6,7,53]. A feltételezések szerint N atom eltávolítása csak telített szénhidrogénből lehetséges [52], ezért először a szomszédos aromás gyűrűnek kell hidrogéneződnie (iii lépés).…”
Section: A Hdn Reakciók Mechanizmusaunclassified
See 1 more Smart Citation